EFL STUDENTS’ PERCEPTION ABOUT MACHINE TRANSLATION - Marito, Setia; Ashari, Erwin (Universitas Riau Kepulauan, 2017)
Machine Translation become as alternative to know the meaning of foreign language. Machine Translation was used to translate word, phrase, sentence, pharagraph. text translation was made as a general description and a consederation to get understanding. Machine Transalation can be used as dictionary, too. It is easier to find word by using Machine Translation rather than dictionary. The purpose of using it; to ensure the meaning, to know the meaning and to be more practice. But, Machine Translation leaded them to a confused situation, because sometimes the grammar and structure were different from what they knew and learned, so it made them confused deciding the correct one. Another effect was making them became lazy to open dictionary, to memorize new words.son their problem on using machine translation covers structure/grammar and several words such as idiom.Keywords: Machine Translation, Machine Translation Problems, Structure/Grammar Case.